Feeling Valued and Adding Value: A Participatory Action Research Project on Co-creating Practices of Social Inclusion in Kindergartens and Communities - Heimburg, Dina von; Langås, Susanne Vollan; Ytterhus, Borgunn (Frontiers in Public Health, 2021)
Background: Contemporary public health problems connect to the social determinants of health, with a growing recognition of social inclusion as imperative to sustainable development. In this quest for social inclusion, early childhood and families are of particular interest. Although co-creation is suggested as viable path to support well-being, less is known how social inclusion might be co-created in practice. The aim of this study was to explore how Participatory Action Research (PAR) can be a tool for transformative practices in a local community, pointing to kindergartens as meeting places for recognizing social inclusion as a common value in early childhood. Methods: A qualitative PAR study was embedded in a Norwegian municipality as an integrated part of their local public health work. The study involved a wide range of participants and stakeholders in three kindergartens and the wider community. Together, we explored potentials for co-creating social inclusion to achieve well-being through cycles of transformative actions and reflections. Reflexive thematic analysis was applied to generate patterns and themes in the data. Results: The participants formulated and took on ownership to an inclusive agenda through the PAR-process. Acts of inclusion was framed by an intersection between political aims of achieving health and well-being for all and public value co-creation unfolding at the level of the place, in the context of the Norwegian welfare regime. To feel valued and adding value was seen as important aspects for social inclusion. Four themes were generated from analysis; 1) Co-creating a shared vision of inclusive communities, 2) Becoming aware and empowered through caring, sharing and collaboration, 3) Places and spaces of inclusiveness in kindergartens and beyond and 4) Valuing and practicing inclusion, and signs of transformative change. Conclusions: Through the PAR process, parents, kindergartens employees, community members and policy makers appear to have opened a creative toolbox for inclusive and transformational change through formulating and co-creating inclusion and well-being as public values. The results suggest that local actors might support adaptive social systems to taking on relational responsibility for inclusive processes and outcomes in the pursuit of well-being for all.